Innovative Technologies in Professional Education - Shermuxamedova, Surayyo Nigmatullayevna (Journal of Higher Education and Academic Advancement, 2024)
This article provides information about innovative technologies of professional education from the point of view of effective integration into the educational process for training competitive specialists.